Enemies and brothers in arms: Candida albicans and gram‐positive bacteria. (14th September 2016) - Förster, Toni M.; Mogavero, Selene; Dräger, Antonia; Graf, Katja; Polke, Melanie; Jacobsen, Ilse D.; Hube, Bernhard
Abstract: Candida albicans is an important human opportunistic fungal pathogen which is frequently found as part of the normal human microbiota. It is well accepted that the fungus interacts with other components of the resident microbiota and that this impacts the commensal or pathogenic outcome of C. albicans colonization. Different types of interactions, including synergism or antagonism, contribute to a complex balance between the multitude of different species. Mixed biofilms of C. albicans and streptococci are a well‐studied example of a mutualistic interaction often potentiating the virulence of the individual members. In contrast, other bacteria like lactobacilli are known to antagonize C. albicans, and research has just started elucidating the mechanisms behind these interactions. This scenario is even more complicated by a third player, the host. This review focuses on interactions between C. albicans and gram‐positive bacteria whose investigation will without doubt ultimately help understanding C. albicans infections.